Умумий ўрта таълимда бошланғич синф ўқувчилари жисмоний тарбиясини шакили ва мазмуни - қувондиқов, акмал (Физическое воспитание, спорт и здоровье, 2022)
The article provides some scientific and theoretical information on the importance of the form and content of physical education of primary school pupils in general secondary education.